MANAGEMENT OF BENIGN NEOPLASM AR GLOSSUS ET VESTIBULUM IN PATIENTS AT SULTAN FATAH HOSPITAL DEMAK - Rizqi, Aulia Adila; Rahmah, Laily; Rahmawati, Hety; Maulana, Rifan Irham; Wafiroh, Arkhamatul; Amiza Zam, Syarifah Nova (Universitas Muhammadiyah Semarang, 2024)
Tumor is a mass or abnormal growth of tissue in the body. Tumors are divided into 2 namely benign tumors and malignant tumors. Manifested by a lump, although some cases show ulceration, pain and bleeding. The size of the lesions ranged from 0.8 – 5.0 cm (mean 2.6 cm) and the lesions were usually asymptomatic. Primary Health Research (Riskesdas), the prevalence of tumors in Indonesia shows an increase from 1.4 per 1000 population in 2013 to 1.79 per 1000 population in 2018. A 62 year old male patient came to the Oral Surgery Clinic at Sultan Fatah Hospital, Demak Regency on April 28, 2023 with complaints of lumps on the edges of the tongue and gums the size of corn kernels, the color is similar to the surrounding area since the last 1-2 years. Examination of the tongue feels springy when touched, there is a wound at the edge of the mass, and it does not rupture easily but bleeds easily. Panoramic radiographic examination revealed a round opacity parallel to tooth 38. The provisional diagnosis obtained was benign neoplasm of the vestibule and multiple necrosis of the pulp of teeth 24, 27, 38, 43. The planned treatment was excision of the tumor as well as odontectomy of teeth 24, 27, 38 and 43 under general anesthesia.